2017
DOI: 10.1021/acs.jpclett.7b00996
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Construction of Two-Dimensionally Self-Assembled Peptide on Pristine Graphene

Abstract: Peptide assemblies have received significant attention because of their important role in biology and applications in bionanotechnology. Despite recent efforts to elucidate the principles of peptide self-assembly for developing novel functional devices, peptide self-assembly on two-dimensional nanomaterials has remained challenging. Here, we report nature-inspired two-dimensional peptide self-assembly on pristine graphene via optimization of peptide-peptide and peptide-graphene interactions. Two-dimensional pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…On the other hand, a better conservation in the total helical content is observed in the multi-segment system, implying a protective collective action of the peptides. More recently, No et al ( 2017 ) reported nature-inspired two-dimensional peptide self-assembly on G via optimization of peptide−peptide and peptide−G interactions. Atomistic simulations determined the optimal peptide sequence that leads to peptide self-assembly on G, suggesting that the optimal peptide sequence minimizes the peptide−G interaction energy and also the peptide−peptide interaction energy, resulting in stable complexes on G.…”
Section: Computational Modeling and Simulations Of Graphene-interactimentioning
confidence: 99%
“…On the other hand, a better conservation in the total helical content is observed in the multi-segment system, implying a protective collective action of the peptides. More recently, No et al ( 2017 ) reported nature-inspired two-dimensional peptide self-assembly on G via optimization of peptide−peptide and peptide−G interactions. Atomistic simulations determined the optimal peptide sequence that leads to peptide self-assembly on G, suggesting that the optimal peptide sequence minimizes the peptide−G interaction energy and also the peptide−peptide interaction energy, resulting in stable complexes on G.…”
Section: Computational Modeling and Simulations Of Graphene-interactimentioning
confidence: 99%
“…Computational models and molecular dynamics (MD) simulations offer information that is hardly accessible by experiments, and they fill the gap between theories and experiments. Therefore, as an initial step of systematic investigations, we studied how MXene nanosheets with cationic surfaces affect the properties of a bacterial membrane composed of zwitterionic phospholipids by atomistic MD simulation (Figure ). Surprisingly, we observed that the MXene nanosheet induced the formation of a lower fluidity domain in the phospholipid membrane, and the fluidity of the phospholipids in this domain was comparable with the fluidity of phospholipids in the gel phase.…”
mentioning
confidence: 99%
“…results obtained from singlemolecule experiments) but also provide new insights into proteins' dynamics and mechanics, which are still difficult to be observed in experiments due to their limited spatial and temporal resolutions. In addition, these computer simulations may also allow for providing an important design principles for developing a novel materials such as newclass protein materials [160][161][162] and nano-bio composite material [163][164][165] (i.e. material formed by coupling protein material and nanomaterial).…”
Section: Resultsmentioning
confidence: 99%